Kirurško zdravljenje endometrijskega karcinoma - Rakar, Stelio (Zdravniški vestnik, 2003)
Background. Nowadays, endometrial cancer is the most frequent gynecologic malignancy with a relatively good prognosis. The prognosis and the quality of life of these patients can be improved considering the prognostic factors and more rational treatment. Methods. This retrograde analysis comprised 499 patients with endometrial cancer operated at the Department of Obstetrics and Gynecology and then irradiated at the Institute of Oncology in Ljubljana in the period 1995-1999. Results. Most patients had stage I disease (81.4%), goodprognostic histological type (endometroid and adenoacanthoma in 81.3%), well- and moderately differentiated tumors (86%) and early myometrial invasion(72.4%). In the observed period we performed radical hysterectomy "old" Wertheim (Piver II) in only 8.4% of cases, in all other cases simple vaginal or abdominal hysterectomy (in 46.9% with pelvic lymphadenectomy) was done. Adjuvant irradiation was administered to 70% of patients. The analysis of 3- and 5- year survival comprises only 466 patients. The overall 5-year survival was 85.8%, in stage I cases 88.1%. There were no significant differences in survival in stage I cases regarding the type of surgery. In stage I the most important adverse prognostic factors were poor differentiation, deep myometrial invasion and serous-papillary histologic type, whereas lymph node involvement was very rare (less than 1%). Conclusions. For the choice of appropriate surgical treatment of patients withendometrial cancer it is necessary to consider the prognostic factors. In this analysis a more radical surgical procedure did not improve the survival significantly. The usefulness of limphadenectomy in stage I remains open.
Keywords: Bezgavka, ekscizija; Endometrial Neoplasms; endometrij; Endometrijske novotvorbe; ginekologija; Histerektomija; Histerektomija vaginalna; Hysterectomy; Hysterectomy, Vaginal; karcinom; kirurško zdravljenje; Lymph Node Excision; Neoplasm Staging; Novotvorba, stadij; preživetje; Preživetje, analiza; Surgery; Survival Analysis